PERTIMBANGAN UNTUK MELIBATKAN ORANG TUA, KELUARGA DAN MASYARAKAT DALAM PROSES PENDIDIKAN DAN PENGEMBANGAN ANAK - Nirwana, Evi Selva; Suriyanti, Suriyanti; Oktaviana, Ningmas Nindri (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This research aims to explore the considerations involved in involving parents, families and communities in children's education and development. Involving parents and families in children's education not only supports the learning process at school but also plays an important role in the formation of strong character and moral values. In addition, the role of the community as a wider social environment also has a significant impact on children's development. This article discusses various factors that are taken into consideration in optimizing parental and family involvement, such as time constraints, parents' education level and social support from the surrounding community. In this context, the importance of collaboration between schools, parents and communities will be discussed as an effort to create a supportive environment for holistic education. The findings of this study are expected to provide insights for policy makers and educators in designing programs that effectively involve all three elements.